2022
DOI: 10.3390/ijms232113084
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced Expression of ARK5 in Hepatic Stellate Cell and Hepatocyte Synergistically Promote Liver Fibrosis

Abstract: AMPK-related protein kinase 5 (ARK5) is involved in a broad spectrum of physiological and cell events, and aberrant expression of ARK5 has been observed in a wide variety of solid tumors, including liver cancer. However, the role of ARK5 in liver fibrosis remains largely unexplored. We found that ARK5 expression was elevated in mouse fibrotic livers, and showed a positive correlation with the progression of liver fibrosis. ARK5 was highly expressed not only in activated hepatic stellate cells (HSCs), but also … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 45 publications
0
1
0
Order By: Relevance
“…Yang et al (2022) found that NUAK1 induces epithelial mesenchymal transition (EMT) in liver cells and promotes the secretion of inflammatory factors. These can enhance the activation of hematopoietic stem cells, promoting liver fibrosis through the synergistic effect between hematopoietic stem cells and liver cells 23 . However, in the kidneys, it has been shown that silencing of NUAK1 reduces the expression of TGF-β1 and reversing fibrosis of renal tubular cells, thus alleviating the symptoms of renal fibrosis 24 .…”
Section: Discussionmentioning
confidence: 99%
“…Yang et al (2022) found that NUAK1 induces epithelial mesenchymal transition (EMT) in liver cells and promotes the secretion of inflammatory factors. These can enhance the activation of hematopoietic stem cells, promoting liver fibrosis through the synergistic effect between hematopoietic stem cells and liver cells 23 . However, in the kidneys, it has been shown that silencing of NUAK1 reduces the expression of TGF-β1 and reversing fibrosis of renal tubular cells, thus alleviating the symptoms of renal fibrosis 24 .…”
Section: Discussionmentioning
confidence: 99%